A Time-Dependent Drought Index for Non-Stationary Precipitation Series - Yixuan Wang; Jianzhu Li; Ping Feng; Rong Hu (Water Resources Management, 2015)

Age-related changes in photosynthesis and water relations of revegetated Caragana korshinskii in the Tengger desert, Northern China - Jing-Ting Bao; Jin Wang; Xin-Rong Li; Zhi-Shan Zhang; Jie-Qiong Su (Trees, 2015)

Induction of follicular luteinization by equine chorionic gonadotropin in cyclic guinea pigs - Jun-rong Li; Wei Wang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2015)

EGCG induces G-CSF expression and neutrophilia in experimental sepsis - Wei Li; Andrew H. Wu; Shu Zhu; Jianhua Li; Rong Wu; John D’Angelo; Haichao Wang (Immunologic Research, 2015)

Cloning of the A Mating-Type Locus from Lepista nuda and Characterization of Its Genetic Structure - Chengbo Rong; Shuang Zhao; Dengjin Li; Lijuan Wang; Shouxian Wang; Kang Ma; Feng Xu; Yu Liu (Current Microbiology, 2015)

Tetrodotoxin detection and species identification of pufferfish in retail roasted fish fillet by DNA barcoding in China - Nan Li; Qing Shen; Jiahui Wang; Chunhui Han; Rong Ji; Fengqin Li; Tao Jiang (Food Additives & Contaminants: Part A, 2015)

Palaeoproterozoic magmatic–metamorphic history of the Quanji Massif, Northwest China: implications for a single North China-Quanji-Tarim craton within the Columbia supercontinent? - Chao Wang; Rong-She Li; Meng Li; Joseph G. Meert; Yan Peng (International Geology Review, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

ATF6 pathway of unfolded protein response mediates advanced oxidation protein product-induced hypertrophy and epithelial-to-mesenchymal transition in HK-2 cells - Xun Tang; Xiujie Liang; Minhui Li; Tingting Guo; Na Duan; Yue Wang; Guang Rong; Lei Yang; Shaojie Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2015)

Purification and Antioxidant Property of Antioxidative Oligopeptide from Short-Necked Clam ( Ruditapes philippinarum ) Hydrolysate In Vitro - Rong Li; Zui-su Yang; Yu Sun; Li Li; Jia-Bin Wang; Guofang Ding (Journal of Aquatic Food Product Technology, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Activation of the signalling mucin MoM sb2 and its functional relationship with C bp1 in M agnaporthe oryzae - Guanghui Wang; Guotian Li; Shijie Zhang; Cong Jiang; Jun Qin; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary Various surface signals are recognized by M agnaporthe oryzae to activate the P mk1 MAP kinase that is essential for appressorium formation and invasive growth. One of upstream sensors of the P mk1 pathway is the MoM sb2 signalling mucin. However, the activation of MoM sb2 and its relationship with other sensors is not clear. In this study, we showed that the cleavage and transmembrane domains are essential for MoM sb2 functions. Cleavage of MoM sb2 was further confirmed by western blot analysis, and five putative cleavage sites were functionally characterized. Expression of the extracellular region alone partially rescued the defects of M omsb2 in appressorium formation and virulence. The cytoplasmic region of MoM sb2, although dispensable for appressorium formation, was more important for penetration and invasive growth. Interestingly, the M omsb2 cbp1 double mutant deleted of both mucin genes was blocked in P mk1 activation. It failed to form appressoria on artificial surfaces and was non‐pathogenic. In addition, we showed that MoM sb2 interacts with R as2 but not with MoC dc42 in co‐immunoprecipitation assays. Overall, results from this study indicated that the extracellular and cytoplasmic regions of MoM sb2 have distinct functions in appressorium formation, penetration and invasive growth, and MoM sb2 has overlapping functions with C bp1 in recognizing environmental signals for P mk1 activation.

The MADS ‐box transcription factor FgMcm1 regulates cell identity and fungal development in F usarium graminearum - Cui Yang; Huiquan Liu; Guotian Li; Meigang Liu; Yingzi Yun; Chenfang Wang; Zhonghua Ma; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary In eukaryotic cells, MADS ‐box genes are known to play major regulatory roles in various biological processes by combinatorial interactions with other transcription factors. In this study, we functionally characterized the FgMCM1 MADS ‐box gene in F usarium graminearum , the causal agent of wheat and barley head blight. Deletion of FgMCM1 resulted in the loss of perithecium production and phialide formation. The F gmcm1 mutant was significantly reduced in virulence, deoxynivalenol biosynthesis and conidiation. In yeast two‐hybrid assays, FgMcm1 interacted with M at1‐1‐1 and F st12, two transcription factors important for sexual reproduction. Whereas F gmcm1 mutants were unstable and produced stunted subcultures, F gmcm1 mat1‐1‐1 but not F gmcm1 fst12 double mutants were stable. Furthermore, spontaneous suppressor mutations occurred frequently in stunted subcultures to recover growth rate. Ribonucleic acid sequencing analysis indicated that a number of sexual reproduction‐related genes were upregulated in stunted subcultures compared with the F gmcm1 mutant, which was downregulated in the expression of genes involved in pathogenesis, secondary metabolism and conidiation. We also showed that culture instability was not observed in the F vmcm1 mutants of the heterothallic F usarium verticillioides . Overall, our data indicate that FgMcm1 plays a critical role in the regulation of cell identity, sexual and asexual reproduction, secondary metabolism and pathogenesis in F . graminearum .

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Luteolin attenuate the d -galactose-induced renal damage by attenuation of oxidative stress and inflammation - Yuqing Xu; Jingzheng Zhang; Jing Liu; Sai Li; Cheng Li; Wen Wang; Rong Ma; Yi Liu (Natural Product Research, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

The role of Cyclin G1 in cellular proliferation and apoptosis of human epithelial ovarian cancer - Lifei Jiang; Rong Liu; Yingying Wang; Chunmiao Li; Qinghua Xi; Jianxin Zhong; Jian Liu; Shuyun Yang; Juan Wang; Menghui Huang; Chunhui Tang; Zheng Fang (Journal of Molecular Histology, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

Novel Interactive Partners of Neuroligin 3: New Aspects for Pathogenesis of Autism - Chen Shen; Li-rong Huo; Xin-liang Zhao; Pei-rong Wang; Nanbert Zhong (Journal of Molecular Neuroscience, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Determination of tumorigenic Agrobacterium density in soil by real-time PCR assay and its effect on crown gall disease severity - Qian Li; Rong-Jun Guo; Shi-Dong Li; Shi-Fang Li; Hong-Qing Wang (European Journal of Plant Pathology, 2015)

Predicting hybrid fertility from maker-based genetic divergence index of parental varieties: implications for utilizing inter-subspecies heterosis in hybrid rice breeding - Ping Liu; Zhiwu Dan; Zhe Wang; Shaoqing Li; Nengwu Li; Huanxin Yan; Xingxing Cai; Bao-Rong Lu (Euphytica, 2015)

Effects on Pharmacokinetics of Propranolol and Other Factors in Rats After Acute Exposure to High Altitude at 4,010 m - Li Wenbin; Wang Rong; Xie Hua; Zhang Juanhong; Wu Xiaoyu; Jia Zhengping (Cell Biochemistry and Biophysics, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

The Effect of Continuous Blood Purification on the Prognosis of Cardiorenal Syndrome Patients - Fengyu Jia; Peng Rong; Dandan Li; Suxia Wang; Ying Jing; Yanming Ge; Jianzhong Meng (Cell Biochemistry and Biophysics, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

The anti-angiogenic role of discoidin domain receptor 2 (DDR2) in laser-induced choroidal neovascularization - Tong Zhu; Jie Zhu; Xin Bu; Hu Zhao; Shuya Zhang; Yuan Chang; Rong Li; Libo Yao; Yusheng Wang; Jin Su (Journal of Molecular Medicine, 2015)

Determination of selected pharmaceuticals in tap water and drinking water treatment plant by high-performance liquid chromatography-triple quadrupole mass spectrometer in Beijing, China - Mei-Quan Cai; Rong Wang; Li Feng; Li-Qiu Zhang (Environmental Science and Pollution Research, 2015)

Effect of anthracene on the interaction between Platymonas helgolandica var. tsingtaoensis and Heterosigma akashiwo in laboratory cultures - Rong Bi; You Wang; Renjun Wang; Wei Li; Xuexi Tang (Journal of Ocean University of China, 2015)

Relationships between heavy metal concentrations in soils and reclamation history in the reclaimed coastal area of Chongming Dongtan of the Yangtze River Estuary, China - Chao Ma; Rong Zheng; Jiale Zhao; Xiumei Han; Li Wang; Xiaojiang Gao; Chaosheng Zhang (Journal of Soils and Sediments, 2015)

Signals induced by exogenous nitric oxide and their role in controlling brown rot disease caused by Monilinia fructicola in postharvest peach fruit - Jing Ying Shi; Na Liu; Rong Xin Gu; Li Qin Zhu; Chang Zhang; Qing Guo Wang; Zhong Hua Lei; Yun Yun Liu; Ji Yun Ren (Journal of General Plant Pathology, 2015)